Energy drinks: Ergolytic or ergogenic? - Sillivent, J.; Blevins-McNaughton, J.; Peak, K. (International Journal of Exercise Science, 2012)
Despite the growing popularity of energy drinks, many do not realize the negative effects on the cardiovascular system. The purpose of this study was to examine the effects of energy drink ingestion on estimated VO2max, heart rate (HR), systolic and diastolic BP (SBP and DBP, respectively), rate pressure product (RPP), and RPE at rest and during exercise. Seven healthy adults (age: 24.3 ± 3.5 yrs; body mass: = 66.0 ± 2.2 kg) participated in this randomized double blind, crossover study. Subjects ingested a placebo (PL) or Redline (RL) energy drink (240ml; 250 mg caffeine) 40 minutes before maximal graded exercise test (GXT). Estimated maximal oxygen consumption (VO2max) was lower in the RL trial (37.9±5.7 ml·kg-1·min-1) compared to the PL trial (39.7±6.5 ml·kg-1·min-1; P= 0.02). Although no significant differences were noted for the number of ectopic beats (ETB) between the trials, a five to one ratio for the RL and PL existed (RL = 106 total ectopic beats; PL = 21 total ectopic beats). Sub-maximal exercise heart demand (RPP: systolic BP x HR) at the same workload was considerably higher in the RL trial (224.9 ± 39.9 mmHg·bts·min-1; P=0.04) compared to PL (195.8 ± 22.9 mmHg·bts·min-1). Recovery DBP was significantly higher at one min. in the RL trial (51.6 ± 25.1 mmHg) compared to PL (25.4 ± 33.8 mmHg; P=0.05). Based on the results of this study, it was determined that energy drinks lowered estimated VO2max while elevating RPP and recovery DBP.